Current trends in tendinopathy management. Issue 1 (February 2019) - Cardoso, Tanusha B.; Pizzari, Tania; Kinsella, Rita; Hope, Danielle; Cook, Jill L.
Abstract: Tendinopathy (pain and dysfunction in a tendon) is a prevalent clinical musculoskeletal presentation across the age spectrum, mostly in active and sporting people. Excess load above the tendon's usual capacity is the primary cause of clinical presentation. The propensity towards chronicity and the extended times for recovery and optimal function and the challenge of managing tendinopathy in a sporting competition season make this a difficult condition to treat. Tendinopathy is a heterogeneous condition in terms of its pathology and clinical presentation. Despite ongoing research, there is no consensus on tendon pathoetiology and the complex relationship between tendon pathology, pain and function is incompletely understood. The diagnosis of tendinopathy is primarily clinical, with imaging only useful in special circumstances. There has been a surge of tendinopathy treatments, most of which are poorly supported and warrant further exploration. The evidence supports a slowly progressive loading program, rather than complete rest, with other treatment modalities used as adjuncts mainly targeted at achieving pain relief.